TANGGUNG JAWAB SEKUTU PERSEKUTUAN KOMANDITER ATAS PENJUALAN ASET PASCAPAILIT SEBAGAI ACTIO PAULIANA - Denaya Annisa (Fakultas Hukum Universitas Udayana, 2023)
The purpose of this research is to determine the judge's consideration of the post-bankruptcy addendum of lease agreement and factory management as actio pauliana and the responsibilities of CV partners in bankruptcy regarding to the cancellation of addendum. This research uses normative method with statute, conceptual, and case approach. This research shows that based on judge's consideration, the addendum of the agreement that made post-bankruptcy could be canceled through actio pauliana, because it is not an obligation for the debtor and is detrimental to creditors, so the cancellation of the agreements and addendum can be done by court to avoid losses for the creditors in bankruptcy. The second party who suffers losses in the addendum could become a creditor to obtain the fulfillment of their rights as promised in the addendum by CV partners. In fulfilling CV debts, active partners are jointly and severally responsible to their personal assets, while passive partners are only responsible for the capital contributed to the CV if they do not take any parts in managing the CV with active partners.